The Methods of Uthman bin Foduye's Teaching and Preaching in Islamizing the Pre-Colonial Nigerian Society - Gokaru, Shuaibu Umar; Ali @ Mat Zin, Aizan Bt; Abdul Hamid, Ahmad Faisal bin (Online Journal of Research in Islamic Studies, 2016)
Uthman bin Foduye (1754-1817) was born and raised in Hausaland (presently Northern Nigeria) where the inhabitants lived in a darkness of ignorance about Islam. This study is based on qualitative approach. The method of documentary used in the data collection. On the other hand, it employs the usage of documentary and inductive in data analysis. The findings reveal that Uthman bin Foduye has distinctive methods in teachings and preaching towards Islamizing the pre-colonial Nigerian society. He was distinguished with these methods among other scholars of Hausaland who had earlier before him intended to Islamize their societies but failed due to the lack of systematic methods in teachings and preaching. Additionally, the findings have further revealed that Uthman has successfully Islamized Hausaland and mobilized his disciples in a peaceful manner without quarrelling with the rulers of the land. It might be added that he, however, charged his disciples to base their lives according to the Islamic Shari'a, where upon, QurÂ’an and Sunnah of the Prophet (PBUH) are their main sources of reference. This research recommended that contemporary Islamic scholars should try to employ systematic methods in teaching people to understand the pure Islamic religion, which forbids associating any partner with Almighty Allah. They should also have to have bravery, tolerance, and sincerity like that of Uthman bin Foduye in discharging their missionary activities.